The Difference In The Effects Of Combining Core Stability Exercise With Plyometric Training Versus Ladder Training On Improving Speed And Agility In Futsal Extracurricular Students - Kamaluddin, Andi Yuliana; Wahyuni, Nila; Lesmana, Syahmirza Indra (International Journal of Public Health Excellence (IJPHE), 2025)
Futsal is a sport that requires speed and agility. However, the physical fitness measurements of futsal extracurricular students at MAN 2 Soppeng indicated below average speed and agility. This study aims to compare the effects of combining core stability exercise with plyometric training and ladder training on improving speed and agility. This was a true experimental study with the randomized match two groups design involving 22 students, divided into two groups of 11. Group 1 received CSE+PT, while Group 2 received CSE+LT for 6 weeks. Speed was measured using a 30-meter sprint test, and agility was assessed with the Illinois Agility Test. Both groups showed significant improvements in agility (p=<0.001). For speed, Group 1 showed p=0.003 and Group 2 p=<0.001. However, there was no significant difference between groups for speed improvement (p=0.061), while there was a significant difference in agility (p=<0.001). This study suggests CSE+LT is more effective in enhancing agility).